Multiple Salinity Equilibria and Resilience of Persian/Arabian Gulf Basin Salinity to Brine Discharge - Ibrahim, Hamed D.; Xue, Pengfei; Eltahir, Elfatih A. B. (Frontiers in Marine Science, 2020)
The Persian/Arabian Gulf is the most important region for seawater desalination. Surrounding countries produce about 50 % of global desalinated seawater. If Gulf salinity significantly rises because of desalination effluent (brine), marine ecosystems and the water supply for many population centers will be threatened. In order to quantify current and future impacts of seawater desalination on Gulf salinity and avoid costly environmental problems, it is vital to first examine the present Gulf salinity state and its response to salinity perturbation (i.e. determine its stability). Here, using a coupled Gulf-Atmosphere numerical climate model, we test the hypothesis that the Gulf has a single stable equilibrium state under the current climate. Simulations with different initializations under identical external forcing show that the natural coupled Gulf-Atmosphere system may exhibit a mixture of unstable and stable equilibrium salinity states. When continuous salinity perturbation is added to the simulations, results show that the present Gulf equilibrium state, characterized by annual mean basin-average salinity of about 40.6 g/kg, is stable. We conclude that Gulf basin salinity is resilient to present brine discharge activities under the current climate.